Ecology of Knowledge in Rural Education as epistemological and societal alternative: the SIECS - Maria Elizabeth Souza Gonçalves (Universidade Federal do Norte do Tocantins, 2018)
With the theme "Land, Labor and Education", the Interterritorial Seminary of Rural Education in Semiarid was hold in the city of Juazeiro, Bahia, from 17 to 19 November, 2016, pointing out in its organizing process a pluralist perspective by thinking engagemently the knowledge about Rural Education, with the contribution of a plural group that had different knowledge: Academy, Rural Social Movements, Student Movement and Artists. This paper aimed to describe analytically the SIECS experience, using as methodological instruments the documental research in the electronic event page, the personal notes, the collective moments of evaluation moments and Political Letter of SIECS, showed at the end of the event. Related to ecology of knowledge (Santos, 2010), the event aimed both to home the comprehension that scientific progress in this knowledge field depends on its dialogue with the traditional knowledge and the Arts and to qualify Rural Education as scientific field with hard knowledge area. The results pointed out the SIECS as contra-hegemonic space to strengthen the struggle by land, education, quality of life for all, constructed in a descolonial perspective where place, time and being are seen in different power relationships.